Apoptosis of CD8+ T cells is mediated by macrophages through interaction of HIV gp120 with chemokine receptor CXCR4 - Herbein, Georges; Mahlknecht, Ulrich; Batliwalla, Franak; Gregersen, Peter; Pappas, Todd; Butler, John; O'Brien, William A.; Verdin, Eric (Nature (London), 1998)
CD8-positive T cells are thought to play an important role in the control of infection by human immunodeficiency virus (HIV) as a result of their cytotoxic activity and by releasing soluble factors 1 , 2 . In AIDS patients, the absolute number of CD8 + T lymphocytes is decreased in peripheral blood 3 , 4 and their turnover rate is increased, suggesting that there is more cell renewal and cell death occurring 5 . Anti-retroviral therapy raises CD8 + T-cell counts in HIV-infected patients 6 , 7 , 8 . Here we report that the death rate of CD8 + T cells by apoptosis increased markedly during HIV infection of peripheral blood mononuclear cells in vitro . Apoptosis is induced in a dose-dependent manner by recombinant envelope glycoprotein gp120 from HIV strain X4, or by stromal-derived factor-1 (SDF-1), the physiological ligand of the chemokine receptor CXCR4. Apoptosis is mediated by the interaction between tumour-necrosis factor-α bound to the membrane of macrophages (mbTNF) and a receptor on CD8 + T cells (TNF-receptor II, or TNFRII). The expression of both of these cell-surface proteins is upregulated by HIV infection or by treatment with recombinant gp120 or SDF-1. Apoptosis of CD8 + T cells isolated from HIV-infected patients is also mediated by macrophages through the interaction between mbTNF and TNFRII. These results indicate that the increased turnover of CD8 + T cells in HIV-infected subjects is mediated by the HIV envelope protein through the CXCR4 chemokine receptor.